THE INFLUENCE OF FINANCIAL RATIOS ON BANKING PROFIT GROWTH IN INDONESIA: COVID-19 ERA - Restyasih, Rinzia Revy; Fitri, Nabilla Lexsa (Jurnal Pijar, 2024)
This study aims to find out the influence of financial performance on banking profit growth in Indonesia during the Covid-19 pandemic. Researchers used quantitative approach with descriptive methods. The population is banking companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic, while the samples were selected by purposive technique. The data used is secondary data obtained from the Annual Financial Report published on the Indonesia Stock Exchange (IDX). Statistical test using SPSS with multiple linear regression model. The findings of this study are Return on Equity (ROE) and Operating Expenses and Operating Income (BOPO) have a positive effect on profit growth, while the Capital Adequancy Ratio (CAR) provides a strong indication as a potentially important factor even though it is not yet statistically significant and other variables (Return on Assets, Net Interest Margin, and Loan on Deposit Ratio) do not have a significant effect on profit growth in banking companies listed on the Indonesia Stock Exchange in the 2020-2023 Covid-19 pandemic era .